English Language Attrition Levels and Language Maintenance Efforts among Indonesian Non-English Department Students - Uswatun Khasanah, Yunita; Widiati, Utami; Tresnadewi, Sintha; Nunuk Wulyani, Anik (Register Journal, 2024)
In the EFL context, the primary linguistic environment for learners is a formal classroom in which they receive input, feedback, and opportunities to practice with teachers and other learners. However, as learners graduate from schools, they might no longer have access to such an environment and thus be deprived of the main intake to support acquisition and retention, which makes them susceptible to language attrition. This study aims to explore the levels of attrition experienced by 165 multilingual non-English department students 30 months after graduating from their secondary schools, the possible factors associated with attrition, and the predictive power of some language maintenance efforts (LMEs) on English attrition. The participants took standardized English tests, that is, Test 1 and Test 2 administered within a 24-month interval and responded to a questionnaire about LMEs. A paired t-test was used to establish a link between attrition level and the identified factors. A multiple linear regression analysis was conducted to determine the predictive power of LMEs for attrition. The results show that learners with different proficiency levels experience different levels of attrition. Factors like attitude and motivation showed different degrees of correlation with attrition. A negative correlation was found in the three dimensions of LMEs: entertainment, literacy activity, and academic activity. Contrary to popular literature on first- and second-language attrition, the dimension of social interaction has a very low predictive power for foreign-language attrition.